2017
DOI: 10.2147/ndt.s130818
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity to computers and the Internet among patients with schizophrenia spectrum disorders: a cross-sectional study

Abstract: PurposeInformation and communication technologies have been developed for a variety of health care applications and user groups in the field of health care. This study examined the connectivity to computers and the Internet among patients with schizophrenia spectrum disorders (SSDs).Patients and methodsA cross-sectional survey design was used to study 311 adults with SSDs from the inpatient units of two psychiatric hospitals in Finland. The data collection lasted for 20 months and was done through patients’ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 48 publications
2
18
1
Order By: Relevance
“…The utilization of information technology was found to extend to almost the entire population of Hong Kong, which is a modern city [ 57 ]. We found that the frequency of internet use by most of our participants was higher than those reported in the United States [ 29 ] and Finland [ 30 ]. The high accessibility to the internet could be explained by the affordable and extensive coverage of the internet network [ 58 ].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…The utilization of information technology was found to extend to almost the entire population of Hong Kong, which is a modern city [ 57 ]. We found that the frequency of internet use by most of our participants was higher than those reported in the United States [ 29 ] and Finland [ 30 ]. The high accessibility to the internet could be explained by the affordable and extensive coverage of the internet network [ 58 ].…”
Section: Discussioncontrasting
confidence: 57%
“…The majority of these people spend more than 1 hour per day on a computer and a mobile phone, and the main purpose of use includes surfing the internet, social networking, and playing web-based games. One study in Finland revealed that only 55% of the people with schizophrenia had a computer and even fewer had access to internet connection [ 30 ]. A recent pilot study investigated the usage of mobile and computer devices among people with severe mental illness [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the qualitative nature of our process, the elicitation of feedback from multiple stakeholder groups (ie, clinicians in addition to patients), the multiple opportunities given to reflect and contribute, the active engagement of participants in the adaptation process, and the factors related to context (eg, different characteristics of the employment and health sector). In addition, many of our patient participants had sociodemographic characteristics that may have facilitated receptivity to Horyzons, for example, several had high levels of education, which has been associated with active use of the internet [ 20 ], seeking medical information on the web [ 21 ], and the depth and breadth of engagement with web-based interventions [ 22 ] among those with psychosis and other psychotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Along with facilitating direct contact between service users and clinicians [ 1 , 2 ] digital monitoring and health intervention tools have been recently applied in the treatment of psychosis with promising effects [ 3 - 8 ]. Given the inverse relationship between the age and use of digital health technology [ 9 ], computer literacy [ 10 , 11 ], and mobile phone ownership or use [ 12 - 14 ], mobile health (mHealth) systems may be particularly advantageous when applied to an early psychosis population vulnerable to relapse [ 15 ]. Levels of technology use in psychosis are similar to that in the general population [ 12 , 3 ], and people with psychosis express favorable attitudes toward digital health interventions (DHIs) and self-management systems [ 3 ].…”
Section: Introductionmentioning
confidence: 99%